Modelling neuroimmune interactions using organotypic slice cultures - Mbobo, Buchule (Division of Chemical Pathology, 2017)
Tuberculosis predominantly manifests in the form of a pulmonary infection, but may spread out into other parts of the body and is then referred to as extrapulmonary tuberculosis (EPTB). One form of EPTB is an infection of the central nervous system (brain & spinal cord), CNS-TB. Although CNS-TB is relatively rare, accounting for about 5% of EPTB, it is characterised by high morbidity and mortality, particularly for children and immunosuppressed individuals. To examine the effects of a Mycobacterium tuberculosis infection of neural tissue, researchers have hitherto relied on two animal models namely, in vivo intracranial infections or in vitro culturing with dissociated neural cells. Both models have yielded crucial insights concerning CNS-TB but each have limitations e.g. lack of access to the brain during infection in vivo and absence of the 3D organizational tissue structure in vitro. This study investigated the effect of the vaccine strain for tuberculosis, Bacille Calmette-Guerin (BCG) on neural tissue using the model of organotypic hippocampal slice cultures; an in vitro model that overcomes the previously mentioned obstacles. The study sought to expound on immunological and electrophysiological responses to the infection. A viable and moderate BCG infection was established in the hippocampal slice cultures, confirmed by colony forming units enumeration and immunohistochemistry. However, immunological analysis using ELISA found that BCG infection did not change the production levels of cytokines and elicit a distinguishable immune response. To examine the neuronal function during BCG infection, whole-cell patch clamp technique was applied to the hippocampal slice cultures. The neuronal intrinsic properties were not significantly different between infected and non-infected slices. However, tuberculin PPD (M. tuberculosis extract) moderately and transiently had a depolarizing effect when 'puffed' directly onto neurons. In conclusion, organotypic slice cultures are suitable for the investigation of cellular interactions and neural functions in CNS-TB, and the neuronal impact of PPD warrants further investigation.